SPORTS ORIENTATION OF CHILDREN AS A FACTOR OF INVOLVEMENT IN SPORTS - Lubysheva, L.I. (Theory and Practice of Physical Culture, 2022)
The article is devoted to the problem of involving children in sports. The significance and role of sport in the formation of significant mental, physical qualities of a person, his social attitudes are substantiated. It is noted that the leading vector of introducing children to sports is sports orientation, built on the formation of interest, ideas about sports, motor experience, and the creation of unified starting opportunities for beginner athletes. It is emphasized that, given the cultural, heuristic and pedagogical potential of sports, it is necessary to skillfully use it in educating the younger generation. Sports orientation should be purposefully carried out by teachers with children, starting from preschool age.